Exploring the Emotions of Single International Students in Hong Kong Facing the COVID-19 Pandemic - Suprihatin (Kehok),; Istiqomah, Lilik; Meilani, Rini Intansari; Khoiriyah, (Journal of International Students, 2020)
This narrative study aims to explore the emotional experiences of international students in Hong Kong during the COVID-19 pandemic. Data in this study were garnered from the results of interviews with two single female students who were completing their doctoral studies at a public university in Hong Kong. We analyzed the interview data thematically with the Hargreaves’s emotional geography framework (2001a, 2001b). Findings showed that the COVID-19 pandemic affected the emotional experience of international students in terms of the dissertation guidance process, psychological mental state, relationships with family, finance, and spirituality. This empirical evidence may provide new insight into the role of emotionality in the completion of postgraduate studies during the uncertain and worrying pandemic.